Analysis of the stress-strain state of laminated timber beams reinforced with composite tapes - Mykhaylovskyi, Denis; Komar, Mykola (Academic journal Industrial Machine Building Civil Engineering, 2022)
The use of timber structures is gaining popularity around the world. The main laminated timber constructions are beams, the study of which has received much attention. To increase rigidity and strength, beam structures are reinforced. There are many different methods of reinforcing such structures (steel reinforcement, plates, composite reinforcement, etc.). The least researched one of them is reinforcement with composite tapes. For a further detailed analysis of the stress-strain state of laminated timber elements of rectangular cross-section reinforced with composite tapes, a number of numerical researches were performed using the finite element method in the LIRA-CAD software package using three-dimensional and flat finite elements, taking into account the features of work and structure of laminated timber beams and carbon fiber composite tapes. Therefore, according to the conducted research, this method of reinforcement can be considered effective.
Keywords: composite materials; composite tapes; laminated timber constructions; timber constructions; reinforcement; strengthening